ADAMTS13 and von Willebrand factor assessment in steady state and acute vaso‐occlusive crisis of sickle cell disease. Issue 1 (18th December 2020) - Demagny, Julien; Driss, Aurélie; Stepanian, Alain; Anguel, Nadia; Affo, Louis; Roux, Damien; Habibi, Anoosha; Benghezal, Sandrine; Capdenat, Sophie; Coppo, Paul; Driss, Françoise; Veyradier, Agnès
Abstract: Background: Sickle cell disease (SCD) is characterized by vaso‐occlusive crisis (VOC), acute chest syndrome (ACS) and multiorgan failure (MOF) complicated by thrombosis. Von Willebrand factor (VWF) is a strong marker of SCD‐related endothelial injury. Objectives: To decipher the role of VWF and its specific‐cleaving metalloprotease, ADAMTS13, in the vaso‐occlusive and thrombotic process of SCD. Patients/Methods: We investigated the VWF antigen (Ag), ADAMTS13 activity, ADAMTS13 Ag and ADAMTS13 IgGs in a cohort of 65 patients with SCD prospectively enrolled in a 20‐month period from three centers. Patients were divided into two groups: an asymptomatic group (n = 30) with treated or untreated SCD at steady state, and a VOC/ACS group (n = 35) with SCD with VOC/ACS requiring either medical management or intensive care management for MOF. Results and Conclusions: VWF:Ag levels were increased (median, 167 IU/dL; interquartile range [IQR], 124 ‐ 279), especially in patients with VOC SCD (227 IU/dL; IQR, 134‐305; P  = .04), and positively correlated with inflammatory markers ( P  < .02). Median ADAMTS13 activity was normal (70 IU/dL; IQR, 60‐80), but 7 patients exhibited a partial deficiency between 25 and 45 IU/dL. ADAMTS13 activity/VWF:Ag ratio, however, did not change during VOC. Median ADAMTS13:Ag was slightly decreased (611 ng/mL; IQR, 504‐703) with no significant difference between groups. Surprisingly, ADAMTS13 IgGs were detected in 33 (51%) of our patients. We conclude that, in SCD, VWF:Ag and nonrelevant ADAMTS13 IgGs may reflect the severity of the inflammatory vasculopathy enhancing vaso‐occlusive and thrombotic complications.